2021
DOI: 10.3390/ijms22157945
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Age Affects MSC Senescence In Vitro—A Systematic Review

Abstract: The use of mesenchymal stromal cells (MSCs) in regenerative medicine and tissue engineering is well established, given their properties of self-renewal and differentiation. However, several studies have shown that these properties diminish with age, and understanding the pathways involved are important to provide regenerative therapies in an ageing population. In this PRISMA systematic review, we investigated the effects of chronological donor ageing on the senescence of MSCs. We identified 3023 studies after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Organisms continuously repair injured tissues and retard senescence-related processes owing to the distinctively functional characteristics of the MSCs that extensively reside within various tissues and organs [ 15 ]. Unfortunately, age and disease are key factors for MSC senescence in vivo, and internal and external differences in cellular environments accelerate MSC senescence in in vitro culture, both of which negatively affect their capacity for immunosuppression, differentiation, and migration, ultimately reducing the efficacy of self-repair and transplantation in MSCs [ 7 , 14 , 49 , 50 , 51 ]. Oja and colleagues indicated that human BMSCs ceased proliferation at the fifth to ninth passage of clinical-grade cultures and exhibited typical senescence phenotypes, such as a hypertrophic and flat morphology, the activation of cell cycle kinase inhibitors p16 and p21, a decreased proliferation rate, and an enhanced activity of SA-β-gal [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Organisms continuously repair injured tissues and retard senescence-related processes owing to the distinctively functional characteristics of the MSCs that extensively reside within various tissues and organs [ 15 ]. Unfortunately, age and disease are key factors for MSC senescence in vivo, and internal and external differences in cellular environments accelerate MSC senescence in in vitro culture, both of which negatively affect their capacity for immunosuppression, differentiation, and migration, ultimately reducing the efficacy of self-repair and transplantation in MSCs [ 7 , 14 , 49 , 50 , 51 ]. Oja and colleagues indicated that human BMSCs ceased proliferation at the fifth to ninth passage of clinical-grade cultures and exhibited typical senescence phenotypes, such as a hypertrophic and flat morphology, the activation of cell cycle kinase inhibitors p16 and p21, a decreased proliferation rate, and an enhanced activity of SA-β-gal [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Care would be needed when using ABT-263 in terms of cytotoxic effects; however, when compared with FACS, ABT-263 pretreatment is easy, inexpensive, and requires no special equipment. Senescence of various MSC types is also known to be accelerated during aging of individuals and during in vitro serial passaging of MSCs in culture [ 32 , 37 ]. ABT-263 pretreatment could also be beneficial in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…MSC morphological changes, with the increased expression of genes that codify for focal adhesion and actin cytoskeleton organization, have been shown [ 94 ]. A recent systematic review has revealed an increase in SA-βGAL activity in senescent MSCs, particularly in the expression of p53, p21 and p16, Rb, ROS, and NF-κB, together with decreased proliferation markers [ 102 ]. The prolonged expression and activity of any of these regulatory components is sufficient to induce senescence [ 4 ], initially reducing the proliferation rate until the characteristic cell growth arrest of senescent cells is reached [ 70 , 103 , 104 ].…”
Section: The Effect Of Leukemic Cells On Mesenchymal Stem Cell Proper...mentioning
confidence: 99%